Dekonstruksi Perjanjian Dalam Hukum Perkawinan Islam - Arif, Muhammad; Widya Sari (Al Ahkam, 2023)
AbstractThis paper aims to examine the essence of the contract in marriage, the taklik divorce as an agreement, polygamy agreements as mandated in the Marriage Law and property agreements in marriage. Normatively, everything is understood based on an agreement either by using the term contract or the agreement itself. This is a literature review (library research). The data analysis method used is content analysis. The results of this study indicate that contract law norms as mandated in Article 2 KHI, basically cannot be perceived as an agreement but are "a statement of handing over of responsibility from the guardian to the prospective husband. Taklik Divorce as an integral part of the marriage/marriage series is very counterproductive to Article 1320 of the Civil Code and the principles of agreements such as the principle of consensuality and the principle of freedom of contract. Polygamy agreements are basically accommodated in laws and regulations, but in principle are very counterproductive to the principle of justice and the orientation of the marriage itself as mandated in Article 1 of the Marriage Law and further emphasized by Article 2 KHI. Property agreements in marriage are perceived to prioritize the concept of materialism in marriage and are very counterproductive to Article 1 of the Marriage Law and Article 2 of the KHI. Based on the several points above, the legal norms related to these issues should be reviewed as an effort to place marriage on its true purpose and essence.Keywords: Deconstruction, Agreement, Islamic Marriage Law